Energy-efficient secure cooperative based image transmission in wireless sensor networks using different system models - Al-Hayani, Bilal Salih Abed (My University, 2020)
Nowadays, wireless sensor networks (WSNs) are widely used for the different multimedia applications in which the data in multimedia form (e.g., images and videos) are captured by visual sensors and transmitted to base station or destination nodes, and such networks commonly called as wireless multimedia sensor networks (WMSN) to transmit high-quality image over sensor nodes needing high throughput, less bit error rate (BER) and more transmission rate with less consumption of energy parameters. For WMSNs, energy efficiency and security are two major concerns as the high dimensional and sensitive digital images consume more processing capabilities of sensor nodes. Thus, it requires the development of energy-aware multimedia processing algorithms to transmit digital images in WMSN without compromising security and quality. The cooperative image transmission methodology over sensor networks is proven to be an effective solution in the recent past. In the first contribution of the thesis, we propose energy efficiency and quality-aware multi-hop one-way cooperative image transmission framework based on image pre- processing technique, wavelet-based two-dimensional discrete wavelet transform (2DDWT) methodology, and decode and forward (DF) algorithm at relay nodes. In the second contribution, along with the image quality improvement and compressive sensing (CS) technique, the security of CS data has been achieved. The one-way DF based cooperative secure digital image transmission model over WSNs uses advanced terminologies for image compression called optimization JPEG2000 compression, and modified Elliptic curve cryptography (ECC) encryption is proposed. In the final contribution of this thesis, one-way image transmission in the MIMO communication model is proposed for secure digital image transmission over the WSNs. The simulation results of each contribution of this thesis are presented in comparison with the new state-of-art methods. The obtained results prove that the proposed digital image transmission models provide an improvement in energy efficiency, security and service quality (QoS)
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: Efficient one-way multi-hop cooperative image transmission; Rayleigh fading channels; Wireless sensor networks